Control, use and ownership of big data: A reciprocal view of customer big data value in the hospitality and tourism industry. (October 2020) - Line, Nathaniel D.; Dogru, Tarik; El-Manstrly, Dahlia; Buoye, Alex; Malthouse, Ed; Kandampully, Jay
Abstract: While the large-scale harvesting of consumer data is a common practice in the hospitality and tourism industries, the seemingly unassailable right of companies to collect and share consumer data is not without critics. The purpose of this paper is to explore the nature of data-based value co-creation under varying conditions of consumer control and benefits. Academic and press articles were used to explore the nature of big data value co-creation in a wide range of hospitality, tourism, and other industries. A forward-looking approach was adopted by considering the implications of policy and technology as key mechanisms for sharing the power dynamic regarding the ownership, control and use of personal data. The results suggest that reciprocal big data value creation can be seen as a function of the level of benefit and control afforded to consumers regarding the use of their data. Four types of reciprocal big data value creation are proposed. Highlights: The issues associated with large-scale data harvesting are reviewed. Big-data is conceptualized as a value catalyst in the hospitality/tourism industries. A conceptualization of reciprocal big data value is discussed. A control/benefits typology of big data value reciprocation is proposed. Creating reciprocal big data value is discussed in terms of technology and policy.